2013
DOI: 10.18632/oncotarget.1165
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role for Early Growth Response-1 in the Transcriptional Regulation of miR-20b in Breast Cancer

Abstract: ABSTRACT:Transcriptional regulation of miRNAs that control the pathogenesis of breast cancer remains largely unknown. Here, we showed that ionizing radiation, a known breast carcinogen, triggered the differential expression of miR-20b in mammary tissues. We identified several GC-rich consensus binding motifs for the zinc finger transcription factor early growth response-1 (EGR1) in miR-20b promoter. miR-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 58 publications
3
57
0
1
Order By: Relevance
“…Egr1 is expressed at high levels in transformed differentiated cells and functions as a proto-oncogene in certain tumor types. [33][34][35] Consistently, we find high levels of Cdk6 mRNA paralleled by a statistically significant upregulation of Egr1 in transformed BCR-ABL p1851 cells (supplemental Figure 6A). Chromatin immunoprecipitation (ChIP) analysis revealed the presence of CDK6 at the Egr1 promoter at levels comparable to its binding to the p16…”
Section: Cdk6 Directly Regulates Egr1 Expression In Hematopoietic Cellssupporting
confidence: 73%
“…Egr1 is expressed at high levels in transformed differentiated cells and functions as a proto-oncogene in certain tumor types. [33][34][35] Consistently, we find high levels of Cdk6 mRNA paralleled by a statistically significant upregulation of Egr1 in transformed BCR-ABL p1851 cells (supplemental Figure 6A). Chromatin immunoprecipitation (ChIP) analysis revealed the presence of CDK6 at the Egr1 promoter at levels comparable to its binding to the p16…”
Section: Cdk6 Directly Regulates Egr1 Expression In Hematopoietic Cellssupporting
confidence: 73%
“…The higher levels of EGR1 transcription factor in HFDO when compared to CDO tumors, while counter to its previously reported tumor suppressor function (Huang et al , 1997), is consistent with its recently reported role as an oncogene (Li et al , 2013) and in enhancing drug-resistance of breast cancer cells (Tao et al , 2013). Moreover, the lack of Dox treatment effects on the frequencies of basal (CD29 hi CD24 + ), luminal (CD29 lo CD24 + ) and tumor-initiating (CD29 hi CD24 + Thy1+) epithelial subpopulations in HFDO, and the higher transcript levels of stem cell markers Notch 1 and Aldh1 in HFDO than in CDO tumors are congruent with the reported positive association between drug insensitivity and expansion of breast cancer stem cells.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, functional analysis indicated that ZNF267 increased the proliferation rate and migration of HCC cells in vitro (Schnabl et al, 2011). In this study, ZNF238 was targeted by over-expressed miR-20b, which was reported to be an oncogenic miRNA (Li et al, 2013). Conversely, ZNF267 was a target gene of the antineoplastic miRNAs -23a and -23b (Goto et al, 2014;Xishan et al, 2014), both of which were downregulated in our study.…”
Section: Discussionsupporting
confidence: 55%